Betwixt and between: conceptual and practical challenges of preventing violent conflict through EU external action. Issue 2 (27th May 2018) - Davis, Laura
ABSTRACT: Conflict prevention is a primary objective of EU external action (European Council, 2011). This article analyses how EU actors understand "conflict prevention" and finds the term is used to mean both a way in which the EU acts in the world, and also a set of discrete activities: conflict analysis, early warning and mediation. Adapting Whitman and Wolff, the article analyses EU capabilities for both concepts of "conflict prevention": to engage, to fund, and to coordinate and cooperate, which contribute to the capabilities to lead and to act. The article demonstrates extensive EU capabilities to engage, to fund and to coordinate and cooperate with third parties in preventing conflict. However, challenges remain, particularly the lack of conceptual clarity on "conflict prevention", leadership, internal coordination and cooperation, and the prioritization of early preventive action, based on early warning, over response to conflicts that have already escalated. The article closes by suggesting ways to mitigate these challenges.